Caracterización molecular de Heliconia sp. Utilizando la técnica RAPD. - Gutierrez y Cols., Freddy (2019)
This work was carried out between the months of July to September 2010 with the objective of molecular characterization of the species heliconia sp using the RAPD molecular marker. For this, we performed the purification of genomic DNA, of the species under study with good results in terms of quality and quantity of purified DNA, which was verified by electrophoretic and spectrophometric methods, the amount of DNA obtained was on average 92.8 ng/ l, also the ratio of average quality was 2.2. For amplification of PCR products was used MT3R initiator, obtaining much polymorphism. PCR products had sizes of 750 bp to 2050 bp. as for the molecular characterization, we performed a dendrogram (UPGMA) using the statiscal sofwar version 2.0 NTSIS. It also obtained the formation of 2 groups (clusters) and 2 leaks where we the appearance  of “apparent duplicates” in some of them, ie they share the same genetic patern with 100% similarity. Also, the value of expected heterozygosity was 0.14, relatively low value, possibly the type of reproduction that has this kind, which is the autogamous.